Simulation of prospective PIRCHE-II molecular matching in Canada: a feasibility study - Sherwood, K. R.; Günther, O. P.; Fenninger, F.; Tran, J.; Lan, J.; Niemann, M.; Sapir-Pichhadze, R.; Keown, P. A. (Frontiers in Immunology, 2026)
IntroductionOrgan allocation to minimize Human Leukocyte Antigens (HLA) disparity between donor and recipient has been shown to improve outcomes but is limited by the enormous HLA diversity. PIRCHE-II in silico model considers the HLA peptide binding characteristics of recipients to quantitate molecular compatibility. Having previously published the feasibility of including B-cell eplets into simplified, simulated match algorithms, here we assess the feasibility of using PIRCHE-II epitope optimised allocation, in a cohort of ~1500 heterogenous renal patients and donors within the National Canadian organ transplant program.MethodsThis test-bed-only analysis provides critical first steps to understanding if prospective matching is indeed feasible, in a Canadian transplant population.ResultsSimplified base-case simulation models optimizing for PIRCHE-II score demonstrate that molecular matching across all 5 HLA gene loci (A, B, C, DR, DQ) is achievable in <10% of patients, and hence would not be realistic for clinical allocation. In contrast, molecular matching with a low PIRCHE-II score at the principal HLA class II DRB1 or DQB1 loci may be achieved in over 90% of patients compared with the base-case scenario.DiscussionIn reality, the precise matching probability is governed by multiple factors including waiting-list size, donor organ factors, and other allocation restrictions (i.e. ABO blood type, presence of anti-HLA antibodies, clinical urgency), which would further impact match probability.